2011
DOI: 10.1007/s10517-011-1486-6
|View full text |Cite
|
Sign up to set email alerts
|

Change in platelet monoamine oxidase activity in the acutest period of ischemic stroke is associated with the degree of neurological recovery

Abstract: We studied monoamine oxidase activity (MAO) in platelets of patients in the acute period of ischemic stroke. Neurological deficit was evaluated by the data of clinical examinations and scales. In 80% patients MAO activity was considerably increased on 3-5 day after stroke. We found a correlation between increased MAO activity on 3-5 day after ischemic stroke and regression of neurological deficit on day 21 after ischemic stroke. The increase in MAO activity during the acute period of ischemic stroke is presuma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…As such, studies have evaluated the isolation of these monoaminergic metabolites post-stroke and found increased concentrations in CSF using high-performance liquid chromatography (HPLC) (Tang et al, 1989; Wester et al, 1987). Additional work by Uzbekov et al (2011) analyzed blood samples from ischemic stroke patients and found increased MAO activity in stroke platelet samples several days after the initial ischemic insult. They suggested that this effect could be a compensatory mechanism to re-establish brain tissue homeostasis, as an increase in stroke monoamine activity is likely due to an increase in monoamine deamination activation and subsequent glutamate-induced excitotoxicity.…”
Section: Monoamine Neurotransmission Disruption Following Strokementioning
confidence: 99%
“…As such, studies have evaluated the isolation of these monoaminergic metabolites post-stroke and found increased concentrations in CSF using high-performance liquid chromatography (HPLC) (Tang et al, 1989; Wester et al, 1987). Additional work by Uzbekov et al (2011) analyzed blood samples from ischemic stroke patients and found increased MAO activity in stroke platelet samples several days after the initial ischemic insult. They suggested that this effect could be a compensatory mechanism to re-establish brain tissue homeostasis, as an increase in stroke monoamine activity is likely due to an increase in monoamine deamination activation and subsequent glutamate-induced excitotoxicity.…”
Section: Monoamine Neurotransmission Disruption Following Strokementioning
confidence: 99%
“…In rodents, MAO was reduced in the brain following 15-min ischemia, and the MAO activity never reached that of control levels during 7 days of reperfusion (Cvejic et al, 1980;Stanimirovic et al, 1994); In contrast, a different study showed that MAO was increased in the brain after a 22-h ischemia (Ansari et al, 2004). In clinical practice, during the acute period of ischemia stroke (3-5 days), MAO was increased in 25 patients compared to control levels, although the standard deviation was very high (Uzbekov et al, 2011). In our study, after 2-h ischemia, the MAO was decreased at 36 h, and salidroside (80 mg/kg) reversed the MAO levels.…”
Section: Discussionmentioning
confidence: 97%
“…In our study, after 2-h ischemia, the MAO was decreased at 36 h, and salidroside (80 mg/kg) reversed the MAO levels. A significant association between MAO activity and neurological deficits has been revealed by dynamic monitoring of patients with ischemia stroke, and the duration of ischemia is a key factor for stroke rehabilitation (Uzbekov et al, 2011;Crunkhorn, 2018). The effect of the dynamic variation of salidroside on MAO during different durations of ischemia is unclear and requires further studies.…”
Section: Discussionmentioning
confidence: 99%